1996
DOI: 10.3354/meps135169
|View full text |Cite
|
Sign up to set email alerts
|

Carbon acquisition and growth of Antarctic sea ice diatoms in closed bottle incubations

Abstract: ABSTRACT. Mixed cultures of 4 polar diatoms regularly found in Antarctic pack ice were grown over 20 d In closed bottles at high light (200 to 250 pm01 photons m-' S-') and at 0°C in order to investigate growth physiology and biomass production under conditions simulating the sea ice habitat during summer. Species tested were: Chaetoceros cf. neogracile, Fragilariopsis c~~lindrus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…On the contrary and consistant with the results of the present study, the operation of CCMs appears ubiquitous in a wide taxonomic range of aquatic phototrophs (see Raven 1991). Thus, the structure of models of phytoplankton growth based solely on di¡usive CO 2 entry (Riebesell et al 1993;Goericke et al 1994, Laws et al 1995) may need to be reconsidered.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…On the contrary and consistant with the results of the present study, the operation of CCMs appears ubiquitous in a wide taxonomic range of aquatic phototrophs (see Raven 1991). Thus, the structure of models of phytoplankton growth based solely on di¡usive CO 2 entry (Riebesell et al 1993;Goericke et al 1994, Laws et al 1995) may need to be reconsidered.…”
Section: Discussionmentioning
confidence: 58%
“…The fact that all species attained 90% of the normalized C· at DIC concentrations of 41.6 mM (and as low as 0.3 mM for P. tricornutum) (¢gure 3b), while the typical seawater DIC concentration is 2.0 mM, presumably re£ects the e¤ciency of algal CCMs. Although di¡usive CO 2 entry may satisfy the demands for photosynthesis (Gleitz et al 1996), de¢nitive evidence for purely di¡usive CO 2 entry in marine microalgae is scarce. On the contrary and consistant with the results of the present study, the operation of CCMs appears ubiquitous in a wide taxonomic range of aquatic phototrophs (see Raven 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The silicate and phosphate concentrations in the brine channels were far below common half-saturation constants for growth (Sommer 1986(Sommer , 1991, and may thus have caused nutrient-limited growth together with faster uptake of dissolved silicon than nitrate in the batch cultures. However, in the same manner that the different nutrient affinities can cause species succession, active pathways of inorganic carbon acquisition may constitute an important factor driving algal species succession, especially within the brine-channel habitat of sea ice (Gleitz et al 1996). During decreasing CO 2 concentration, indicated by increasing pH values in the cultures, the photosynthetic carbon demand may exceed diffusional CO 2 supply, especially for larger algae.…”
Section: Discussionmentioning
confidence: 99%
“…may have been more successful than larger species of the genera Nitzschia or Thalassiosira. Gleitz et al (1996) observed in an Antarctic sea-ice diatom (Chaetoceros cf. neogracile), the physiological ability to actively assimilate HCO 3 -at CO 2 (aq) concentrations < 0.5 µM and pH > 9.5.…”
Section: Discussionmentioning
confidence: 99%
“…Similar rates were determined for Chaetoceros cf. neogracile (Gleitz et al 1996). For Pseudo-nitzschia sp.…”
Section: Discussionmentioning
confidence: 99%